Foraging by Polybia (Trichothorax) ignobilis (Hymenoptera, Vespidae) on flies at animal carcasses - Gornes, Leonardo; Gornes, Guilherme; Oliveira, Helena G.; Morlin, Jose J.; Desuo, Ivan C.; Silva, Iracerna M. da; Shima, Sulene N.; Von Zuben, Claudio J. (Soc Brasileira Entomologia, 2007)
Foraging by Polybia (Trichothorax) ignobilis (Hymenoptera, Vespidae) on flies at animal carcasses. Proteins for brood nutrition of social wasps are obtained from many prey, including insects (even bees and other wasps), spiders and bits of decaying meat. After being captured and killed, prey are reduced to a shapeless mass and distributed to the brood. Little is known about the foraging activity, especially on this group. Herein we describe the sequence of foraging behaviours of the social wasp Polybia (Trichothorax) ignobilis for hunting flies (Diptera: Calliphoridae and Muscidae) over pig carcasses. To our knowledge, there are few scientific descriptions of prey foraging behaviour on this species.
Keywords: calliphoridae; hunting behavior; muscidae; prey and wasps